2019
DOI: 10.31512/vivencias.v16i30.154
|View full text |Cite
|
Sign up to set email alerts
|

Fatores Que Influenciam a Sanidade E Conforto Térmico De Bovinos Em Sistemas Compost Barn

Abstract: O sistema de produção compost barn é uma das alternativas para os produtores que desejam confinar seus animais. Aliado a alta produtividade, quando bem manejado, garante conforto e bem-estar aos animais. Objetivou-se com essa pesquisa avaliar fatores como pH, crescimento microbiológico, umidade e fermentação que interferem na qualidade do processo de compostagem da cama, além de temperatura interna e acumulo de gazes que comprometem a saúde e bem-estar dos animais. Entre os resultados obtidos estão pontos com … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…According to Damasceno (2020), the studies conducted in Brazil are still scarce in terms of efficiency and quality of alternative materials for the bed available in each region. Piovesan and Oliveira (2020) reported in studies in southern Brazil, that the use oatmeal husk as alternative material resulted significant increase in bedding fermentation and BIT increase, indicating favorable results.…”
Section: Arqmentioning
confidence: 89%
See 2 more Smart Citations
“…According to Damasceno (2020), the studies conducted in Brazil are still scarce in terms of efficiency and quality of alternative materials for the bed available in each region. Piovesan and Oliveira (2020) reported in studies in southern Brazil, that the use oatmeal husk as alternative material resulted significant increase in bedding fermentation and BIT increase, indicating favorable results.…”
Section: Arqmentioning
confidence: 89%
“…The temperature range of 43 to 65ºC can be considered reasonable for the composting process (On-Farm…, 1992). However, as it is a process in which the bedding composes a material that undergoes partial composting (Russelle et al, 2009), reaching optimum temperatures becomes a challenge for milk producers. Following this fact, research using Compost barn in Brazil, including the present work, reported systems in which the ideal temperature range was not reached (Mota et al, 2019;Piovesan and Oliveira, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of confined systems for housing of dairy cows has been growing among dairy farmers, with the aim of optimizing land use, ensuring animal welfare, and providing greater animal comfort [1,2]. Among them, the compost-bedded pack barn (CBPB) housing system, which is characterized by an open bedding area, without individual stalls, and with a bedding surface covered with organic material, is one of the most used confinement systems for dairy cows.…”
Section: Introductionmentioning
confidence: 99%